Spirituality, religiosity, aging and health in global perspective: A review - Zimmer, Zachary; Jagger, Carol; Chiu, Chi-Tsun; Ofstedal, Mary Beth; Rojo, Florencia; Saito, Yasuhiko (SSM - population health, 2016)
Persistent population aging worldwide is focusing attention on modifiable factors that can improve later life health. There is evidence that religiosity and spirituality are among such factors. Older people tend to have high rates of involvement in religious and/or spiritual endeavors and it is possible that population aging will be associated with increasing prevalence of religious and spiritual activity worldwide. Despite increasing research on religiosity, spirituality and health among older persons, population aging worldwide suggests the need for a globally integrated approach. As a step toward this, we review a subset of the literature on the impact of religiosity and spirituality on health in later life. We find that much of this has looked at the relationship between religiosity/spirituality and longevity as well as physical and mental health. Mechanisms include social support, health behaviors, stress and psychosocial factors. We identify a number of gaps in current knowledge. Many previous studies have taken place in the U.S. and Europe. Much data is cross-sectional, limiting ability to make causal inference. Religiosity and spirituality can be difficult to define and distinguish and the two concepts are often considered together, though on balance religiosity has received more attention than spirituality. The latter may however be equally important. Although there is evidence that religiosity is associated with longer life and better physical and mental health, these outcomes have been investigated separately rather than together such as in measures of health expectancy. In conclusion, there is a need for a unified and nuanced approach to understanding how religiosity and spirituality impact on health and longevity within a context of global aging, in particular whether they result in longer healthy life rather than just longer life.